Effects of core‐shell particle growth manners on morphologies and properties of poly(vinyl chloride)/(methyl methacrylate–butadiene–styrene) blends. Issue 1 (2nd August 2014) - Zhou, Chao; Wu, Shuting; Liu, Hua; Wu, Guangfeng
Abstract : A series of methyl methacrylate‐butadiene‐styrene (MBS) core‐shell particles were synthesized by seeded emulsion polymerization. All the MBS particles are designed with the same defined chemical composition, which is a prerequisite for producing transparent blends with poly(vinyl chloride) (PVC). Three different growth manners of core‐shell particles: agglomeration of small styrene‐butadiene rubbers (SBRs) followed by styrene (ST) and methyl methacrylate (MMA) monomers grafting, agglomeration of small MBS particles and traditional MBS with single SBR rubber core, and ST/MMA shells are used. The effects of growth manners of MBS on the properties and deformation mechanism of PVC/MBS blends are studied. It is found that all the MBS particles can toughen the PVC matrix effectively, but different deformation modes are observed: cavitation in large particles, debonding at the PVC/MBS interface, rubber cavitation, and clusters of voids, respectively. In addition, it is found that the stress‐whitening extent is associated with the deformation modes. J. VINYL ADDIT. TECHNOL., 22:37–42, 2016. © 2014 Society of Plastics Engineers